Roles of fMRI and Wada tests in the presurgical evaluation of language functions in temporal lobe epilepsy - Massot-Tarrús, Andreu; Mirsattari, Seyed M. (Frontiers in Neurology, 2022)
Surgical treatment of pharmacoresistant temporal lobe epilepsy (TLE) carries risks for language function that can significantly affect the quality of life. Predicting the risks of decline in language functions prior to surgery is, therefore, just as important as predicting the chances of becoming seizure-free. The intracarotid amobarbital test, generally known as the Wada test (WT), has been traditionally used to determine language lateralization and to estimate their potential decline after surgery. However, the test is invasive and it does not localize the language functions. Therefore, other noninvasive methods have been proposed, of which functional magnetic resonance (fMRI) has the greatest potential. Functional MRI allows localization of language areas. It has good concordance with the WT for language lateralization, and it has been shown to be of predictive value for postsurgical naming outcomes. Consequently, fMRI has progressively replaced the WT for presurgical language evaluation. The objective of this review was to answer the most clinically relevant questions concerning language functions in TLE. First, we will provide context by reviewing the role of the temporal lobe in the language functions. Then, we will evaluate the rationale for the current indications for the WT and fMRI in the presurgical assessments of language, and functional outcomes following various forms of TLE surgery.